Blood Lead Levels in Asymptomatic Opium Addict Patients; a Case Control Study - Ghaemi, Kazem; Ghoreishi, Atefeh; Rabiee, Navid; Alinejad, Samira; Farzaneh, Esmaeil; Amirabadi Zadeh, Alireza; Abdollahi, Mohammad; Mehrpour, Omid (Archives of Academic Emergency Medicine, 2017)
Introduction: One of the newest non-occupational sources of lead contamination is drug addiction, which has recently been addressed as a major source of lead poisoning in some countries. The present study aimed to investigate the blood lead level (BLL) of asymptomatic opium addicts. Methods: This case-control study was conducted during a one-year period to compare BLL of three groups consisting of opium addicts, patients under methadone maintenance therapy (MMT), and healthy individuals. Results: 99 participants with the mean age of 55.43±12.83 years were studied in three groups of 33 cases (53.5% male). The mean lead level in opium addicts, MMT and control groups were 80.30 ± 6.03 μg/L, 67.94 ± 4.42 μg/L, and 57.30±4.77 μg/L, respectively (p=0.008). There was no significant difference in BLL between MMT and healthy individuals (p=0.433) and also between opium addicts and MMT individuals (p=0.271).Oral opium abusers had significantly higher lead levels (p = 0.036). There was a significant correlation between BLL and duration of drug abuse in opium addict cases (r=0.398, p=0.022). The odds ratio of having BLL ≥ 100 in oral opium users was 2.1 (95% CI: 0.92 - 4.61; p = 0.43). Conclusion: Based on the result of present study, when compared to healthy individuals, opium addicts, especially those who took substance orally had significantly higher levels of blood lead, and their odds of having BLL ≥ 100 was two times. Therefore, screening for BLL in opium addicts, particularly those with non-specific complaints, could be useful.